Improving physician referral for tobacco cessation clients of Tobacco Cessation Clinic in South India - Mrudu, Herbert; Riyaz Basha, S; Shashidhar S Basagouda; Subhas, GT (Universiti Kebangsaan Malaysia, 2012)
The major burden of tobacco related diseases is borne by developing countries. Tobacco cessation is an important step in preventing mortality and morbidity due to tobacco related diseases. The objective of the study was to assess the profile of tobacco users utilizing the services of the district anti tobacco cell in Bangalore.A cross sectional study was carried out in 2009. Total of 122 persons above 18 years old, current tobacco users and who were motivated to quit were interviewed by a trained medical social worker. Information about the sociodemographic profile of the clients, details of tobacco use and nicotine dependence levels using Fagerstrom score was collected. SPSS 16.0 software was used for data analysis. The results have been presented using descriptive statistics and ANOVA tests.The study population was comprised of exclusively males. The mean age was 34.9 years. Seventy four percent (73.8%) were smokers while 26% were users of smokeless tobacco products. Fagerstrom scores showed that majority of tobacco users (54% of smokers and 63% of smokeless tobacco users) had moderate to high nicotine dependence. Most of the clients were self-referred. The average pack years of tobacco use and the mean Fagerstrom score were higher in the physician referred group indicating that physicians have access to tobacco users who could benefit the most from tobacco cessation efforts.Clients attending tobacco cessation clinics tend to have moderate to high tobacco dependence. Health care providers need to put in more efforts to refer tobacco users to tobacco cessation services. Improved physician awareness could help in stepping up tobacco cessation efforts.